Jenis-jenis Burung di Daerah Pasui Kecamatan Buntu Batu Kabupaten Enrekang - Andika Saputra, Hasyimuddin; Sijid, St. Aisyah; Saputra, Andika (Al-Hayat: Journal of Biology and Applied Biology, 2019)
Birds are living organisms classified into the Kingdom Animalia, phylum Aves and including organisms that possess similar characteristics with body cover in the form of feathers and can fly. The aim of this study was to determine the diversity of bird species found in Pasui Village, Buntu Batu District, Enrekang Regency. This research was conducted at Pasui watershed. Birdwatching is done by cruising method at three different stations. The results of this study found 14 bird species classified into 5 orders, 11 families and 13 genera. The bird species obtained are Haliastur indus, Collocalia esculenta, Egretta alba, Chalcophaps indica longirostris, Streptopelia chinensin, Corvus enca, Dicaeum aureolimbatum, Eruthrura hyperythra, Lonchura Malacca, Lonchura punctulata, Passer montanus, Pycnonotus aurigaster, Acridontheres javanicus, Zosterops pelpepbrosus.